Cognitive ability to know colour concepts through method simple science experiments in early children - Afifa, Tazkia Syafira; Mangkuwibawa, Hilman; Kurnia, Aam (Kepompong Children Centre Journal, 2024)
Ability to know colour is one aspect of ability. It is an essential cognitive function for brain development in children at an early age. Improving the ability to know colour must supported with adequate methods and facilities, but based on conditions in the field, fewer children still understand draft colour with good Research objectives This is to increase the ability of cognitive children to know draft colour through method simple science experiment. The research used is Classroom Action Research in nature collaborative. Amount of samples from the study: This totalled 11 people. The data collection method used is sheet observation (checklist). Data analysis techniques were carried out quantitatively. Research results show that cognitive knowledge of draft colour can increase with method simple science experiments. This matter is proven by Mark's ability cognitive child with an average value of 38 with the predicate is very lacking. As for the implementation process activity method experiment For increasing cognitive child seen from teacher activities and activities, children in cycle I and Cycle II experienced enhancement that is average percentage of implementation Teacher activity in cycle I reached 67.85% with predicate sufficient, and the average percentage of implementation activity children in cycle II reached 79.85% with predicate Good. after applied activity simple science experiments, abilities know color in group B experienced enhancement from cycle I was 42.20 to cycle II amounted to 71.39 pages This prove that activity simple science experiment can improve ability cognitive child.